Comparison of Pain Experience among Patients Using Super Elastic Nickel-Titanium Vs Copper Nickel-Titanium Archwires During Alignment Stage - Machibya, Ferdinand Mabula; Msungu, Protas John; Mlangwa, Matilda Mtaya Mlangwa; Eladius Laswai Daniel, Eladius Laswai Daniel (Orthodontic Journal of Nepal, 2025)
Introduction: Pain and discomfort associated with teeth movement during the early phase of orthodontic treatment are major concerns for many orthodontic patients. The aim of this study was to compare the pain experience among patient undergoing orthodontic treatment using Super Elastic NiTi (SE NiTi) and Copper NiTi (Cu NiTi) arch-wires during the alignment phase. Materials and Methods: A prospective randomized study was carried out among patients who were in the alignment stage of fixed orthodontic treatment, using two different types of arch wires, SE NiTi or Cu NiTi. Eight-six participants were recruited conveniently in the study, and randomly allocated to either of the study groups. Fixed orthodontic treatment was then initiated with 0.014-inch archwire in both groups. Participants were followed for pain assessment using a modified McGill Pain Questionnaire with Visual Analogue Scale (VAS) for the duration of 7 days. Data were analyzed by SPSS Statistics version 25 with a p-value set at <0.05. Pain comparison between two groups was done using Wilcoxon Signed Rank test and Mann Whitney U test. Results: Three participants were lost to follow up and one participant was omitted from the analysis. Therefore, total of 82 participants were analyzed, 41 participants from each of the study group. Participants from both groups reported pain experience during the initial phase of fixed orthodontic treatment. The pain experience was highest 6 to 12 hours after insertion of the initial archwires in both groups. The majority of the participants reported a gradual decrease in pain intensity over time, with the rate of decline been relatively faster in SE-NiTi group. Conclusion: There was no significant difference between SE NiTi and Cu NiTi in pain experience.